FoodMicroDB: A microbiome database for composition and time‐series research in food - Yahui Li; Hujie Lyu; Haifei Yang; Zhicheng Ju; Chuang Ma; Huiyu Hou; Yao Wang; Yuanping Zhou; Yunyun Gao; Junbo Yang; Shanshan Xu; Defeng Bai; et al. (iMetaOmics)
Abstract Microorganisms are crucial for food fermentation, preservation, and safety, directly impacting human health. The number of studies on the food microbiome has surged recently, along with a substantial increase in data. However, there is a notable lack of databases specialized for this field. To address this gap, we developed Food Microbiome Database (FoodMicroDB), a platform aimed at enhancing the reusability and accessibility of food microbiome data through comprehensive data management and data visualization tools. FoodMicroDB aggregates 6358 amplicon data from 108 meta‐taxonomic projects covering 62 foods, and harbors 4710 taxa of bacteria, archaea, and fungi. The collected data were consistently analyzed and curated, then visualized using versatile utilities, including unique tools for visualizing microbial composition and time‐series microbiome data. It also includes advanced modules for microbial abundance analysis, cross‐host abundance comparison, and cross‐food analysis. FoodMicroDB will be a valuable resource platform for the food microbiome research field. The database is freely accessible at: https://www.bic.ac.cn/FoodMicro/.